2018
DOI: 10.1371/journal.pone.0208001
|View full text |Cite
|
Sign up to set email alerts
|

“Oh oobe doo, I wanna be like you” associations between physical activity of preschool staff and preschool children

Abstract: ObjectivePhysical activity contributes to prevent serious diseases and ailments, and previous research indicates that lifestyle habits are likely to track from early childhood to adulthood. 90% of Norwegian children aged 1–5 are enrolled in preschools, and preschool staff can play an important role in children’s activity levels. This study’s aim was to identify whether any associations exist between preschool staff’s characteristics (initiative, participation, attitudes, and activity levels) and children’s act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 60 publications
2
50
1
2
Order By: Relevance
“…The study also showed that the physical activity levels of the children and the staff were positively correlated, as the staff's physical activity level was also measured with an accelerometer. On the other hand, there was no correlation found using the measuring methods applied in the analysis of responses to questionnaires relating to individual staff attitudes, initiatives and participation and the physical activity level of the children (Fossdal et al 2018). This is in contrast to other studies, which show that positive encouragement and involvement by preschool staff is associated with higher activity levels in children (Brown et al 2009;Gubbels et al 2011;Mikkelsen 2011).…”
Section: Introductioncontrasting
confidence: 66%
“…The study also showed that the physical activity levels of the children and the staff were positively correlated, as the staff's physical activity level was also measured with an accelerometer. On the other hand, there was no correlation found using the measuring methods applied in the analysis of responses to questionnaires relating to individual staff attitudes, initiatives and participation and the physical activity level of the children (Fossdal et al 2018). This is in contrast to other studies, which show that positive encouragement and involvement by preschool staff is associated with higher activity levels in children (Brown et al 2009;Gubbels et al 2011;Mikkelsen 2011).…”
Section: Introductioncontrasting
confidence: 66%
“…However, most previous research on the topic are based on qualitative approaches. Thus far, only one Norwegian study has explored accelerometer assessed associations between preschool teachers' and children's levels of MVPA during preschool hours [44]. This study demonstrated that there was a statistically significant association between preschool teacher's aggregated levels of MVPA and preschool children's individual levels of MVPA.…”
Section: Comparison With Previous Researchmentioning
confidence: 78%
“…However, there is a lack of studies among the preschool population. Only one Norwegian study has used objectively measured PA in both preschool teachers' and children and found a small, but statistically significant association, between preschool teachers' and preschool children's levels of PA during preschool hours [26]. More studies with objective measure on both preschool teachers and children are imperative to confirm the potential association between preschooler's PA and preschool teachers' PA.…”
Section: Introductionmentioning
confidence: 99%
“…Teacher-led sessions are usually preplanned, with guided participation of children; all the children in a group usually conduct similar activities, allowing less freedom for children’s individual choice of activities 14. However, other studies support teacher-led activities, claiming they increase children’s movement and activity levels compared with free-play sessions 48 54 55. Therefore, essential is determining the most effective type of social influence, adult-initiated or child-initiated, in decreasing children’s ST. For instance, children with particular temperament traits may benefit more from adults’ than peers’ role modelling.…”
Section: Discussionmentioning
confidence: 99%